Judicial independence: The master narrative in sentencing practice - Jamieson, Fiona (Criminology & criminal justice, 2021)
This article draws on biographical narrative accounts of retired Scottish judges to provide insight about the operation of judicial independence in the routine practice of criminal justice. This oblique and often reified legal concept is given new meanings and understandings through the lived experiences of retired judicial actors, demonstrating its role as the ‘master narrative’ of the judiciary in their routine sentencing work. This research points to some of the adaptive judicial strategies necessary for the maintenance and reinforcement of the concept in the context of the everyday challenges of sentencing practice. It is argued that although judicial independence represents an aspirational conception of judicial work, this symbolic value also carries important meanings and has material effects in sentencing practice. Moreover, the boundaries of the judicial role in daily criminal practice may be less sharply defined than strong ‘Olympian’ interpretations of judicial independence would otherwise suggest.